Characterization of microbial communities in heavy crude oil from Saudi Arabia - Albokari, Majed (Ann Microbiol, 2014)
The complete mineralization of crude oil into carbon dioxide, water, inorganic compounds and cellular constituents can be carried out as part of a bioremediation strategy. This involves the transformation of complex organic contaminants into simpler organic compounds by microbial communities, mainly bacteria. A crude oil sample and an oil sludge sample were obtained from Saudi ARAMCO Oil Company and investigated to identify the microbial communities present using PCR-based culture-independent techniques. In total, analysis of 177 clones yielded 30 distinct bacterial sequences. Clone library analysis of the oil sample was found to contain Bacillus, Clostridia and Gammaproteobacteria species while the sludge sample revealed the presence of members of the Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Clostridia, Spingobacteria and Flavobacteria. The dominant bacterial class identified in oil and sludge samples was found to be Bacilli and Flavobacteria, respectively. Phylogenetic analysis showed that the dominant bacterium in the oil sample has the closest sequence identity to Enterococcus aquimarinus and the dominant bacterium in the sludge sample is most closely related to the uncultured Bacteroidetes bacterium designated AH.KK.